The Dark Readings of National Literature: Two Cases from the Early Years of Costa Rican Gothic Writing - Calvo Díaz, Karen Alejandra (2014)
The Latin American context, on the modalities o Gothic writing, has had a serial challenge such as the production of texts as the reception and construction of the literary criticism. By placing the terror narrative in countries like Costa Rica, it’s necessary to definite, in advance, the concept of Gothic literature, because it has uneven implications on the continent which originated and supported this same mode in Europe. In this sense, the task of this dissertation reflects about how the notion of the Gothic has been built in the literature of our country and what writers; thematic and discursive strategies instituted a dialogue with terror. This discussion hopes to establish a chronology of this Costa Rican storytelling as well as its essential aspects that characterize it. Also, the theme of transgression and otherness and intertextuality are the most interesting aspects of reading proposed here.